2019
DOI: 10.3390/app9163229
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Variations of Hao-Dependent Nitrifying and Nir-Dependent Denitrifying Microbial Communities in Ammonium-Graduated Lake Environments

Abstract: Biological nitrification and denitrification play significant roles in nitrogen-associated biogeochemical cycles. However, our understanding of the spatial scales at which microbial communities act and vary is limited. We used gene-specific metagenomic PCR to explore changes in nitrifying and denitrifying microbial communities within pristine lake and its branches, where the ammonium and dissolved organic carbon (DOC) concentrations form a gradient. The biomarkers hydroxylamine oxidoreductase and nitrite reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Arenimonas is a complete denitrifier as well [88]. While Thermanaerothrix is known to harbor NO 2 − reducing gene, nirS, its denitrification capacity is not yet confirmed [89]. Detecting these indicators involved in diverse N metabolisms can be explained by the inorganic N deficiency being a major ecological pressure in unfertilized soils.…”
Section: Indicators Of N Fertilizationmentioning
confidence: 99%
“…Arenimonas is a complete denitrifier as well [88]. While Thermanaerothrix is known to harbor NO 2 − reducing gene, nirS, its denitrification capacity is not yet confirmed [89]. Detecting these indicators involved in diverse N metabolisms can be explained by the inorganic N deficiency being a major ecological pressure in unfertilized soils.…”
Section: Indicators Of N Fertilizationmentioning
confidence: 99%
“…The lake regions with the highest amounts of NO 3 and NH 3 showed the highest abundance of hao, suggesting the association of this gene with the eutrophication process. Is it possible that the physicochemical conditions of the soil submitted to the application of vinasse in this period were similar to a eutrophication process such as that described in Zhao et al (74)? Analyzing the oxidoreductase enzymes that correspond to the hao gene family, Nitrosomonas (AOB), which is related to N 2 O emissions by nitrification (75), had the greatest number of sequences in NVT7.…”
Section: Discussionmentioning
confidence: 80%
“…In this study, one of the genes that showed the greatest response to NV was hao, which encodes the oxidoreductase enzyme in the nitrification process (HAO) (72,73). Zhao et al (74) quantified the hao gene associated with nitrifying Bacteria in a lake that received domestic sewage. The lake regions with the highest amounts of NO 3 and NH 3 showed the highest abundance of hao, suggesting the association of this gene with the eutrophication process.…”
Section: Discussionmentioning
confidence: 99%